Deciphering the Pharmacological Potentials of Callicarpa longifolia Lam. by In vitro and In vivo Approaches - Mina, Sadia Tasnim; Ashrafi, Sania; Adib, Mohiminul; Ahmed, Firoj; Kuddus, Md Ruhul (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Callicarpa longifolia Lam., an important medicinal plant of Bangladesh has been subjected for pharmacological investigations to justify the traditional uses of this plant species. The crude methanol extract of aerial parts of C. longifolia and its different Kupchan fractions were evaluated for in vitro antimicrobial, anti-thrombotic, membrane stabilizing, cytotoxic, and in vivo antidiarrheal activities in mice model. All the test samples exhibited significant antimicrobial efficacy, evidenced by the zone of inhibition ranging from 9.0-13.0 mm against the test organisms in disc diffusion technique. The various solvent fractions of C. longifolia showed anti-thrombotic activities in a range of 10.47 ± 0.37% to 29.94 ± 0.85%. Among all, the chloroform fraction showed significant anti-inflammatory property in both heat - and hypotonic solution induced hemolysis. During cytotoxicity test, the plant samples showed a concentrationdependent lethality against live brine shrimp nauplii as compared to standard vincristine sulfate. At the 3rd hour of study, a significant 76.0% reduction in castor oil-induced diarrhea (p <0.05) was observed following an oral administration of the crude methanol extract at a dose of 400 mg/kg. The observed pharmacological potentials of this plant necessitate comprehensive investigation to isolate and characterize its chemical constituents, as well as to elucidate their mechanistic pathways to delineate therapeutic efficacy. Dhaka Univ. J. Pharm. Sci. 24(2): 177-186, 2025 (December)